Urgent and evaluative behaviours according to the risk level in dri-ving situations. - Megías, Alberto; López-Riañez, María; Cándido, Antonio (Anales de Psicología / Annals of Psychology, 2013)
Risky driving situations require, in most cases, decision-making of an urgent nature, differing in this sense from those behaviours that would be classified as evaluative behaviour, which, for example, an observer may carry out. To explore the distinction between evaluative and urgent behaviours, and study under what conditions these differences may be caused, we designed a subjective risk scale based on taxonomy of risky driving situations. This study shows no relationship between the assessment of the situation and the urgent behavioural decision that the situation demands. Urgent behaviours were more conservative and differences in reaction times were found to depend on the level of risk of the situation. This opens up the possibility that our actions are not always in accordance with our evaluations. The differences can be explained, according to the characteristics of this task and taking into account the level of risk involved in the situation. This data could be an important basis for the design of future programs of road safety and driver training, focusing on driver learning and training through the execution of urgent behaviours.